THE EFFECT OF USING PICTURE SERIES ON READING COMPREHENSION OF THE SECOND YEAR STUDENTS OF SMPN 40 PEKANBARU - Hendra, Lola Novita; ', Afrianto; ', Supriusman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims at finding the effect of picture series on reading comprehension of the second year students of SMPN 40 Pekanbaru. The method used in this study was quantitative research and the research design was quasi-experimental study. The researcher used Cluster Random Sampling technique to choose the sample. For 165 students of the population, class VIII B was chosen as the experimental class and VIII D as control class. The instrument of this research was in form of multiple choices test for pre-test and post-test. The test was narrative text and there were 30 multiple choice items for each test. The researcher used formula t-test to analyze the data. The result of this study shows that there was a significant difference on students’ reading comprehension of narrative text by using picture series and without using picture series. The mean score for experimental class was 61.5 (pre-test) and 83.8 (post-test). The mean score for control class was 71.8 (pre-test) and 82 (post-test). It can be seen that on the df =81 in the degree of significance 5%, the value of degree significance is 1.98. By comparing the value to and tt the result showed that to is higher than tt (to>tt = 5.44>1.98). The alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Therefore It can be concluded that there is a significant effect of using picture series on reading comprehension of the second year students of SMPN 40 Pekanbaru.Key words: Effect, picture series, reading comprehension